Decomposing Intergenerational Income Elasticity: The Gender-differentiated Contribution of Capital Transmission in Rural Philippines. (October 2015) - Bevis, Leah E.M.; Barrett, Christopher B.
Highlights: We decompose intergenerational income elasticity (IGE) into four capital transmission pathways. Maternal education is the parent capital most strongly associated with IGE. Naïve IGE estimates are indistinguishable for sons and daughters. Sons' IGE is explained entirely by parent capital transmission. Daughters' IGE persists even after controlling for parent and daughter capital. Summary: Using longitudinal data from rural Philippines, we decompose intergenerational income elasticity (IGE) into five distinct pathways: intergenerational transmissions of health, education, land, and spouse education capital, plus residual correlation in productivity. Intergenerational human capital transmissions from mothers are stronger than those from fathers; maternal education is the parental capital most strongly associated with IGE. While naïve IGE estimates are indistinguishable for sons and daughters, the pathways that generate these results differ strikingly. For sons, IGE is entirely explained by parent-to-child capital transmission. By contrast, strong income correlation exists between daughters and parents even after controlling for parent and child capital endowments.